Human Adaptive Mechatronics and Human-System Modelling. (4th March 2013) - Suzuki, Satoshi; Igarashi, Hiroshi; Kobayashi, Harumi; Yasuda, Tetsuya; Harashima, Fumio
Several topics in projects for mechatronics studies, which are 'Human Adaptive Mechatronics (HAM)' and 'Human-System Modelling (HSM)', are presented in this paper. The main research theme of the HAM project is a design strategy for a new intelligent mechatronics system, which enhances operators' skills during machine operation. Skill analyses and control system design have been addressed. In the HSM project, human modelling based on hierarchical classification of skills was studied, including the following five types of skills: social, planning, cognitive, motion and sensory-motor skills. This paper includes digests of these research topics and the outcomes concerning each type of skill. Relationships with other research activities, knowledge and information that will be helpful for readers who are trying to study assistive human-mechatronics systems are also mentioned.